Artistic activity and its role in the aesthetic response of middle school students - Hira Abdul Jabbar Star Lafta; Saleh Ahmed Mahidi Al-Fahdawi (الاكاديمي)
Artistic activities are one of the most prominent types of arts in which the learner can express his feelings and emotions. These activities include various fields, including the art of drawing, design, and other artistic fields that contribute to building the learner’s personality from all psychological, mental, emotional, and social aspects. At the top of these aspects is the aesthetic aspect, which is not  It is less important than the aspects that preceded it.